Theorising management accounting practices and service quality: the case of Malaysian health tourism hospital destinations - Hung, Woan Ting (2017)
Private hospitals in Malaysia are now extending their healthcare services to cater for patients travelling from the global market. These organisations are aggressively gearing themselves up to deliver quality services and to demonstrate quality assurance on their services. Hence, service quality strategies and initiatives have become critical for success in hospitals and the way forward. In pursuing quality initiatives, hospitals need to gain access to quality-related information and adopting the appropriate management accounting practices would be an important enabler and facilitator to generate useful management information leading to organisational successes. This study examines the usage of management accounting practices in these hospitals and attempts to develop a management accounting framework that would effectively facilitate the implementation of service quality initiatives pursued. Structured questionnaire was used to gather the perceptions of hospital management on service quality implementation level, usage level of management accounting practices usage and performance level of hospitals. Quantitative methods using MANOVA and structural equation modelling with AMOS were employed for data analysis. The results show that service quality implementation level was not found to be higher in hospitals that have obtained more types of quality achievements as compared to those that have obtained less or no achievements. Hospitals have benefitted from the implementation of quality initiatives related to management, process and analysis. However, such benefit was not found in quality initiatives related to patient care. In terms of the mediating role of management accounting practices, the results show no mediation effect on the impact of patient care on hospital performance. Meanwhile, there was partial mediating effect on the impact of management, process and analysis on hospital performance. Specifically, the mediating effect was found to be stronger from the advanced accounting practices compared to the basic accounting practices. The findings lead to a conclusion that adopting the appropriate management accounting practices would effectively facilitate hospitals in their quality pursuits. Limitations of this study and recommendation for future research are presented.